A monastery in “Barrios Altos” “Nustra Señora del Prado” - Scaletti, Adriana (2013)
This article seeks to present the beginnings of interdisciplinary work focused on monastic ensemblesof the Barrios Altos area in the historic center of Lima, Peru. The exemplary case taken for thegeneral introduction to the topic is the set of Nuestra Señora del Prado, founded in 1640. Theapproach is given from the perspectives of history, architecture and civil engineering, and is aproduct of a course taught by and directed towards architects and engineers at the PontificalCatholic University of Peru.